A national carbon dioxide emission abatement scenario: potentials and strategies. (4th August 2014) - Turk, V.; Pahernik, Z.
The Slovene energy system is studied from different decision levels, which means that we are trying to identify coordination effects on subordinate decision levels all the way down to the level of particular business units - energy companies. Such an integrated multilevel and multiobjective approach to energy system policy making is a prerequisite for Slovenia's participation in international activities concerning the investigation of the national potentials of different countries in the process of dealing with global environmental energy issues. The international CHALLENGE Project is an example of the above, and certain results acquired within this project will be used to illustrate some features of the Slovene energy situation with special emphasis on the approach to environmental issues.